Euploidy rate and pregnancy outcomes in preimplantation genetic testing for aneuploidy cycles using progestin-primed ovarian stimulation versus GnRH antagonist protocol - Hu Tan; Li Huang; Wenjuan Liu; Jin Yan; Li Li; Yujiang Wang; Yuqiang Huang; Zonghui Xiao; Fenghua Liu; Xiqian Zhang (Reproductive Biology and Endocrinology)
Abstract Background Previous studies has yielded contradictory findings regarding the relationship between controlled ovarian hyperstimulation (COH) protocol and euploid blastocyst rate. This study aimed to investigate whether progestin-primed ovarian stimulation (PPOS) influences the euploidy rate and pregnancy outcomes in preimplantation genetic testing for aneuploidy (PGT-A) cycles compared to GnRH antagonist protocol. Methods The retrospective study analyzed data from 598 PGT-A cycles conducted between January 2017 and October 2022 utilizing either PPOS (medroxyprogesterone acetate) or the GnRH antagonist protocol. The biopsied trophectoderm from 2218 blastocysts was collected for euploidy analysis via next-generation sequencing. Results Biopsied blastocyst number was comparable between PPOS group and GnRH antagonist group (3.51 ± 2.93 vs. 3.91 ± 3.19, P = 0.116), although PPOS yielded fewer MII oocytes (10.27 ± 6.59 vs. 11.60 ± 6.71, P = 0.015). The euploidy rate (43.3% vs. 45.0%, P = 0.423), aneuploidy rate (36.9% vs. 36.0%, P = 0.127), and mosaic rate (19.4% vs. 17.6%, P = 0.127) were similar between the PPOS and GnRH antagonist protocols. Additionally, PPOS demonstrated comparable pregnancy outcomes to GnRH antagonist protocol, including clinical pregnancy rates (58.1% vs. 59.8%, P = 0.713) and live birth rates (51.1% vs. 46.9%, P = 0.364). But lower miscarriage rate was shown in the PPOS protocol (7.9% vs. 16.8%, P = 0.019). Conclusions The PPOS protocol did not negatively impact euploid blastocyst formation or pregnancy outcomes compared to the GnRH antagonist protocol, indicating that medroxyprogesterone acetate was an alternate option to antagonists for women undergoing PGT-A.